TEACHING NARRATIVE WRITING THROUGH PROBABLE PASSAGE STRATEGY TO ISLAMIC SENIOR HIGH SCHOOL STUDENTS - Novia Fajrina (Edukasi, 2017)
The objectives of this study were to find out whether or not (1) there is a significant improvement on the eleventh grade students’ achievement in writing narrative text before and after the treatment at MA Al-Fatah Palembang, and (2) there is a significant difference on the eleventh grade students’ writing achievement between those who are taught by using Probable Passage strategy and those who are not at MA Al-Fatah Palembang. There were 70 students taken as sample. Each class consisted of 35 students from class XI IPA 2 as experimental group and class XI IPA 1 as control group. The sample of this study was taken by using convenience sampling method. In this study, the writer used quasi experimental design using pretest-posttest non-equivalent groups design. The instrument used collecting the data was writing test. The test was administered twice, as the pretest and posttest for both control and experimental groups. The results of the test were analyzed by using IBM SPSS (Statistical Package for the Social Science) 20. The result showed that (1) there was a significant improvement from students’ pretest to posttest scores in experimental group taught by using probable passage strategy since the p-output (0.000) was lower than (0.05) and t-obtained (25.116) is higher than t-table (2.032) and (2) there was a significant difference from students’ posttest scores in control and experimental groups, since p-output (0.000) was lower than (0.05) and t-obtained (8.243) is higher than t-table (1.995). So, the Ho (the null hypothesis) was rejected and Ha (the alternative hypothesis) was accepted. It means that there was significant difference on students’ writing achievement taught using Probable Passage than students who are taught by using strategy that used by teacher.